Performance analysis of jatropha oil-based polyurethane acrylate gel polymer electrolyte for dye-sensitized solar cells - Rayung, Marwah; Aung, Min Min; Su'ait, Mohd Sukor; Chuah Abdullah, Luqman; Ahmad, Azizan; Lim, Hong Ngee (American Chemical Society, 2020)
Biobased polymers are useful materials in substituting conventional petroleum-derived polymers because of their good properties, ready availability, and abundance in nature. This study reports a new jatropha oil-based gel polymer electrolyte (GPE) for use in dye-sensitized solar cells (DSSCs). The GPE was prepared by mixing jatropha oil-based polyurethane acrylate (PUA) with different concentrations of lithium iodide (LiI). The GPE was characterized by infrared spectroscopy, thermal analysis, lithium nuclear magnetic resonance analysis, electrochemical analysis, and photocurrent conversion efficiency. The highest room-temperature ionic conductivity of 1.88 × 10–4 S cm–1 was obtained at 20 wt % of LiI salt. Additionally, the temperature-dependent ionic conductivity of the GPE exhibited Arrhenius behavior with an activation energy of 0.42 eV and a pre-exponential factor of 1.56 × 103 S cm–1. The electrochemical stability study showed that the PUA GPE was stable up to 2.35 V. The thermal stability of the gel electrolyte showed an improvement after the addition of the salt, suggesting a strong intermolecular interaction between PUA and Li, which leads to polymer–salt complexation, as proven by Fourier transform infrared spectroscopy analysis. A DSSC has been assembled using the optimum ionic conductivity gel electrolyte which indicated 1.2% efficiency under 1 sun condition. Thus, the jatropha oil-based GPE demonstrated favorable properties that make it a promising alternative to petroleum-derived polymer electrolytes in DSSCs.